Zn-Al LAYERED DOUBLE HYDROXIDE AS HOST MATERIAL FOR SUNSCREEN COMPOUND OF p-AMINOBENZOIC ACID - Roto Roto; Iqmal Tahir; Mustofa Mustofa (Indonesian Journal of Chemistry, 2007)
Zn-Al layered double hydroxide can be used as host material for UV active compound p-aminobenzoic acid (PABA), which is having capability to block UV light of sunlight. The formation of Zn-Al-PABA was best developed in which the nucleation process was done at room temperature and followed by hydrothermal treatment at 100 oC.   To make a better product, the molar ratio of Zn to Al to PABA was adjusted to 3:1:1. From the elemental analysis and the content of PABA, it was observed that the product has structural formula of Zn0,745Al0.254(OH)1.650(PABA)0.349. 0.684H2O. The particle size of the powder as estimated using SEM was in the range 100-200 nm. FTIR and XRD proved that the p-amino benzoate ion occupied the interlayer space. This material is expected to have high sun protection factor (SPF).